O Seminário Seráfico Santa Maria e as tensões nas identidades sacerdotal e franciscana no pós-vaticano II (1966-1987) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The objective of this research is to analyze how the daily tensions in the Santa Maria Seraphic Seminary, located in Irati, southwestern Paraná, express difficulties in the reformulation of priestly and Franciscan identities proposed by the Second Vatican Council (1962- 1965). The disputes over these identities generated discussions and debates in the Catholic Church, present in the conciliar documents and in an extensive bibliographical production, and which were deployed in institutions such as the Capuchin Order of Friars Minor, maintainer of the Santa Maria Seminary. From the analysis of the documents of the Second Vatican Council, the Order of the Capuchin Friars Minor, the Santa Maria Seminary, the bibliographic study, as well as interviews and photographs, it is possible to perceive the competitions, uses, consumptions and practices of the discourses produced by the hierarchy among the social subjects involved. Results reveal that identities are not reformulated by decree and that even in environments where the hierarchical position prevails, they are constantly re-signified in the everyday struggles.
Keywords: Igreja Católica; Seminário Santa Maria; Concílio Vaticano II; Capuchinhos; identidades; Catholic Church; Santa Maria Seminary; Second Vatican Council; Capuchins; identities; CNPQ::CIENCIAS HUMANAS::HISTORIA